P3A0 Perdarahan Pasca Persalinan Pervaginam et causa Atonia Uteri: Laporan Kasus - Alandra Rizhaqi Vastra; Ikhlas Taufik; Nurul Islamy (CV. Jasa Sukses Abadi, 2023)
Postpartum haemorrhage is a state of blood loss >500 ml through vaginal delivery, or >1000 ml in caesarean section after delivery. One of the most common causes of postpartum hemorrhage is uterine atony. Uterine atony is a condition of weak uterine tone that causes the uterus to be unable to close the bleeding from the placental implantation site after the baby and placenta are born. Mrs. RF, 36 years old, came to the ER of RS Abdul Moeleok with postpartum bleeding since ± 2 hours before entering the hospital. The patient gave birth vaginally with the help of a midwife and experienced postpartum bleeding due to the absence of adequate uterine contractions (uterine atony) after delivery. The patient was treated with oxytocin and misprostol and the bleeding was resolved.